On the crystal growth of nanoscale schwertmannite - Loan, Mitch; Richmond, William; Parkinson, Gordon (Elsevier Science BV, 2005)
Schwertmannite (Fe16O16(OH)12(SO4)2), commonly found in acidic aqueous systems, forms rapidly into a “hedge-hog” morphology, where nano-dimension whiskers project outwards from an electron-dense interior. Schwertmannite whiskers were recently found to contain the highly disordered and maghemite-like structural components present in ferrihydrite, and on this basis, schwertmannite was postulated to be an intermediate phase (in terms of crystallinity and kinetics of formation) to the least and most crystalline forms of ferrihydrite, 2- and 6-line, respectively. To test this hypothesis and help elucidate the schwertmannite growth mechanism, we reduced supersaturation (a function of pH and ferric concentration) during the crystallization of 2-line ferrihydrite from ferric sulphate liquors. Lower supersaturations resulted in schwertmannite formation, often in an admixture or possibly nucleated on 2-line ferrihydrite aggregates. Alternate experiments performed in the presence of arsenic (as a crystal growth modifier) produced X-ray diffraction (XRD) patterns consistent with admixed ferrihydrite and schwertmannite, but with a morphology where aligned ferrihydrite nanoparticles appeared to approximate the structure of schwertmannite whiskers. We postulate that as similar structural components constitute 2-line ferrihydrite and schwertmannite, but are only minor components in 6-line ferrihydrite, the proportion of each component (with the maghemite-like phase dominating) permits the specific alignment and growth of the intriguing schwertmannite morphology.